2010
DOI: 10.1164/rccm.200905-0799oc
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide Is Increased in the Lower Airway Epithelium of People with Advanced Cystic Fibrosis Lung Disease

Abstract: Immunoreactive ceramide is increased in the lower airway epithelium of people with advanced cystic fibrosis. Detected by mass-spectrometry ceramide species C16:0, C18:0, and C20:0 but not C22:0 are increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
84
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 39 publications
4
84
0
1
Order By: Relevance
“…A study using biochemical techniques, fluorescence microscopy, and mass spectrometry demonstrated that CFTR deficiency results in the accumulation of ceramide in bronchial, tracheal, and intestinal epithelial cells, in alveolar macrophages in cystic fibrosis mice, and in nasal epithelial cells from cystic fibrosis patients (Teichgräber et al, 2008;Zhang et al, 2009;Becker et al, 2010a,b) (Figure 1). The accumulation of ceramide in lung tissues and cells from cystic fibrosis patients or mice has been confirmed by several studies using human transplant material, mouse lung tissue, and cultured cells (Brodlie et al, 2010;Ulrich et al, 2010;Bodas et al, 2011a,b;Caretti et al, 2014;Itokazu et al, 2014). Brodlie et al (2010) provided detailed mass spectrometry data about the accumulation of various ceramide species in the lung and demonstrated the substantial accumulation of the ceramide species C16, C18, and C20 in the lungs of cystic fibrosis patients.…”
Section: Ceramide In Cystic Fibrosismentioning
confidence: 88%
See 1 more Smart Citation
“…A study using biochemical techniques, fluorescence microscopy, and mass spectrometry demonstrated that CFTR deficiency results in the accumulation of ceramide in bronchial, tracheal, and intestinal epithelial cells, in alveolar macrophages in cystic fibrosis mice, and in nasal epithelial cells from cystic fibrosis patients (Teichgräber et al, 2008;Zhang et al, 2009;Becker et al, 2010a,b) (Figure 1). The accumulation of ceramide in lung tissues and cells from cystic fibrosis patients or mice has been confirmed by several studies using human transplant material, mouse lung tissue, and cultured cells (Brodlie et al, 2010;Ulrich et al, 2010;Bodas et al, 2011a,b;Caretti et al, 2014;Itokazu et al, 2014). Brodlie et al (2010) provided detailed mass spectrometry data about the accumulation of various ceramide species in the lung and demonstrated the substantial accumulation of the ceramide species C16, C18, and C20 in the lungs of cystic fibrosis patients.…”
Section: Ceramide In Cystic Fibrosismentioning
confidence: 88%
“…The accumulation of ceramide in lung tissues and cells from cystic fibrosis patients or mice has been confirmed by several studies using human transplant material, mouse lung tissue, and cultured cells (Brodlie et al, 2010;Ulrich et al, 2010;Bodas et al, 2011a,b;Caretti et al, 2014;Itokazu et al, 2014). Brodlie et al (2010) provided detailed mass spectrometry data about the accumulation of various ceramide species in the lung and demonstrated the substantial accumulation of the ceramide species C16, C18, and C20 in the lungs of cystic fibrosis patients. However, at present it is unknown whether distinct ceramide species in the lung are associated with specific pathophysiological changes in CF patients.…”
Section: Ceramide In Cystic Fibrosismentioning
confidence: 88%
“…10,31,32 Furthermore, it has been reported that CERs are important regulators of tumor cell death following exposure to stress stimuli 33,34 and changes in sphingolipid metabolism impact on pancreatic b-cell function. 35 Our in vivo and in vitro findings of CERs and cell death are in agreement with these previous observations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent animal studies offer an attractive novel possibility to treat cystic fibrosis [9]: We demonstrated in mice genetically deficient for Cftr an accumulation of ceramide in tracheal and bronchial epithelial cells [9]. The results were recently independently confirmed and transferred to the human situation demonstrating accumulation of ceramide in bronchial epithelial cells of patients with cystic fibrosis [9,10,11,12]. Ceramide mediates increased death of bronchial epithelial cells resulting in a release of dead cells and finally DNA into the bronchial lumen [9].…”
Section: Introductionmentioning
confidence: 99%